On the stability of additional moons orbiting Kepler-1625 b - Moraes, R. A. [UNESP]; Borderes-Motta, G.; Winter, O. C. [UNESP]; Monteiro, J. [UNESP] (Oxford University Press (OUP), 2022)
Since it was proposed, the exomoon candidate Kepler-1625 b-I has changed the way we see satellite systems. Because of its unusual physical characteristics, many questions about the stability and origin of this candidate have been raised. Currently, we have enough theoretical studies to show that if Kepler-1625 b-I is indeed confirmed, it will be stable. Regarding its origin, previous works indicated that the most likely scenario is capture, although conditions for in situ formation have also been investigated. In this work, we assume that Kepler-1625 b-I is an exomoon and study the possibility of an additional, massive exomoon being stable in the same system. To model this scenario, we perform N-body simulations of a system including the planet, Kepler-1625 b-I, and one extra Earth-like satellite. Based on previous results, the satellites in our system will be exposed to tidal interactions with the planet and to gravitational effects owing to the rotation of the planet. We find that the satellite system around Kepler-1625 b is capable of harbouring two massive satellites. The extra Earth-like satellite can be stable in various locations between the planet and Kepler-1625 b-I, with a preference for regions inside $25\, R_{\rm p}$. Our results suggest that the strong tidal interaction between the planet and the satellites is an important mechanism to ensure the stability of satellites in circular orbits closer to the planet, while the 2:1 mean motion resonance between the Earth-like satellite and Kepler-1625 b-I would provide stability for satellites in wider orbits.
Keywords: planets and satellites: dynamical evolution and stability; planets and satellites: individual: Kepler-1625 b-I